Abdominal ultrasonography inHIV/AIDS patients in southwestern Nigeria. (2008)
"Though the major target of the HIV-virus is the immune system, the frequency of abdominal disorders in HIV/AIDS patients has been reported to be second only to pulmonary disease. These abdominal manifestations may be on the increase as the use of antlretroviral therapy has increased life expectancy and improved quality of life. Ultrasonography is an easy to perform, non invasive, inexpensive and safe imaging technique that is invaluable in Africa where AIDS is most prevalent and where sophisticated diagnostic tools are not readily available. Purpose: To describe the findings and evaluate the clinical utility of abdominal uitrasonography in HIV?AIDS patients in Ibadan. Methods:A Prospective evaluation of the abdominal ultrasonography of 391 HIV-positive patients as well as 391 age and sex- matched HIV-negative patients were carried out at the University College Hospital, Ibadan.Results: Of the 391 cases studied, 260 (66.5%) were females; the mean age was 38.02 years, (range 15-66 years). The disease was most prevalent in the 4th decade with an incidence of 40.4%. Compared with the HIV-negative individual group of patients had a significantly higher proportion of splenomegaly (13.5% vs. 7.7%; p < 0.01), lymphadenopathy (2.0% vs. 1.3%; p < 0.70), and renal abnormalities (8.4% vs. 3.8%; p < 0.02). There were no differences in hepatic and pancreatic abnormalities between the HIV+ and HIV- groups. There were significantly fewer gallstones in the HIV+ group (1.4% vs. 5.1%; p < 0.01). Conclusion:AIDS is a multi-systemic disease and its demographic and clinical pattern remains the same globally. Ultrasond optimally suited for its clinical management especially in Africa. Its accuracy and sensitivity may be much improved with clinico-pathologic correlation which may not be readily available in developing countries; further studies may provide much needed diagnostic algorithms. "